RELIGIOUS ORIENTATION AND MATURITY OF THE VOCATION MEANING AMONG CATHOLIC PRIESTLY CANDIDATES: A STUDY AT ST. PAUL’S MAJOR SEMINARY, KENTUNGAN, YOGYAKARTA - Wika Fitriana Purwaningtyas; Gilas Anti Ampera (UIN Sunan Kalijaga Yogyakarta, 2026)
This study aims to investigate the religious maturity of Catholic seminarians at St. Paul’s Seminary, Kentungan, Yogyakarta. The analysis of religious maturity is intrinsically linked to the relationship and mutual influence between such maturity and the religious vocation of these candidates. Consequently, in addition to evaluating religious maturity, this research explores the underlying meaning of religious vocation. Employing a qualitative methodology, data were gathered through field surveys, utilizing both psychological and phenomenological approaches to religion. Data collection involved direct observation and in-depth interviews, which were subsequently analyzed through the lens of Abraham Maslow’s theory of motivation, William James’s theory of religious maturity, and Antonius Denny Firmanto’s theological framework of vocation. The findings demonstrate that the seminarians exhibit a high degree of religious maturity, characterized by profound spiritual depth and an intimate personal relationship with the Divine. Furthermore, the results indicate that religious maturity significantly reinforces their religious vocation, manifesting as a steadfast and robust commitment to their religious calling. Keyword: religious maturity; reiligous vocation; Catholic seminarians Penelitian ini bertujuan untuk mengetahui bagaimana kematangan beragama calon imam Katolik di Seminari Santo Paulus Kentungan Yogyakarta. Dalam pembahasan kematangan beragama tidak lepas bagaimana hubungan dan pengaruh antara kematangan beragama dan panggilan agama (vocation) calon imam Katolik. Jadi, selain membahas kematangan bergamaa penelitian ini juga akan membahas bagaiamana makna panggilan agama calon imam Katolik. Penelitian ini merupakan penelitian kualitatif yang dilakukan dengan mengumpulkan data dari hasil survei lapangan. Penelitian ini menggunakan pendekatan psikologi agama dan fenomenologi agama. Pengumpulan data dilakukan dengan melakukan observasi, wawancara kepada pihak yang bersangkutan yang kemudian dianalisis menggunakan teori motivasi Abraham Maslow, teori kematangan beragama William James, serta yang terkahir teori teologi panggilan Antonius Denny Firmanto. Hasil penelitian menunjukkan bahwa para imam Katolik di seminari tersebut memiliki kematangan beragama dengan memperlihatkan kedalaman spiritual dan hubungan pribadi yang dekat dengan Tuhan. Selain itu, dalam hubungannya dengan panggilan agama, kematangan beragama memberikan pengaruh berupa komitmen keagamaan yang kuat kepada mereka. Kata kunci: kematangan beragama; panggilan agama; calon imam Katolik